2013
DOI: 10.4161/cc.27355
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents rapamycin-induced upregulation of autophagy and selectively induces apoptosis in TSC2-deficient cells

Abstract: The mammalian/mechanistic target of rapamycin complex 1 (mTORC1) signaling pathway is hyperactivated in a variety of cancers and disorders, including lymphangioleiomyomatosis (LAM) and tuberous sclerosis complex (TSC), which are characterized by mutations in tumor suppressors TSC1 or TSC2. The concern with the use of mTORC1 inhibitors, such as rapamycin or its analogs (rapalogs), is that they cause upregulation of autophagy and suppress the negative feedback loop to Akt, which promotes cell survival, causing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 42 publications
3
49
0
1
Order By: Relevance
“…In this study, we observed that, in TSC2-null cells, the combination therapy prevented rapamycininduced up-regulation of Akt while maintaining inhibition of S6K1 signaling, indicating that this combination therapy can counter hyperactivation of mTORC1 signaling caused by the loss of TSC2. Additionally, resveratrol treatment was able to prevent rapamycin-induced upregulation of autophagy, as evidenced by stabilization of p62, in accord with our previous findings (23). Interestingly, expression of survivin, an inhibitor of apoptosis in TSC2-null cells, was found to correlate with resistance to chemotherapeutic agents (36).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In this study, we observed that, in TSC2-null cells, the combination therapy prevented rapamycininduced up-regulation of Akt while maintaining inhibition of S6K1 signaling, indicating that this combination therapy can counter hyperactivation of mTORC1 signaling caused by the loss of TSC2. Additionally, resveratrol treatment was able to prevent rapamycin-induced upregulation of autophagy, as evidenced by stabilization of p62, in accord with our previous findings (23). Interestingly, expression of survivin, an inhibitor of apoptosis in TSC2-null cells, was found to correlate with resistance to chemotherapeutic agents (36).…”
Section: Discussionsupporting
confidence: 76%
“…In addition, LAM cells seem to be dependent on even the low levels of autophagy because further inhibition of autophagy induces cell death (21). Our previous studies showed that combination therapy of rapamycin with resveratrol was able to block autophagy and induce apoptosis in TSC2-null cells and in cells with mTORC1 pathway hyperactivation (22,23). In this study, we observed that, in TSC2-null cells, the combination therapy prevented rapamycininduced up-regulation of Akt while maintaining inhibition of S6K1 signaling, indicating that this combination therapy can counter hyperactivation of mTORC1 signaling caused by the loss of TSC2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations